Repair Welding: Pengaruh Pengelasan Perbaikan Berulang dengan Kombinasi Proses GTAW dan SMAW terhadap Struktur Mikro dan Sifat Mekanik Baja Tahan Karat Dua Fasa Austenitik-Feritik (Duplex) UNS S31803 - Febi Dwi Antony; Rini Riastuti; Winarto Winarto (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
During welding and also in the stages of fabrication and assembly, welding repair sometimes required to eliminate the welding defects present. This paper focuses on the effect of multiple repair welding on microstructure and mechanical properties of Duplex Stainless Steel UNS S31803. Three times welding repair were performed using combination of Gas Tungsten Arc Welding (GTAW) for root pass up to hot passes and Shielded Metal Arc Welding (SMAW) processes for fill passes up to finish passes. The average of heat input used was of 1.5-1.9 kJ/mm. After welding, the test samples were prepared for microhardness test, Charpy impact test, and microstructural examinations. The results showed that there was a significant reduction of Charpy toughness value due to welding process from 339.22 Joules for base metal to 89.22 Joules and 101.23 Joules for average weld metal and fusion zone consecutively. However, the toughness value between each welding repair showed same pattern with no significant reduction or increment of Charpy impact value. Same pattern also observed on microhardness measurement which revealed no significant fluctuation between each welding repair. Furthermore, the morphology of microstructure present in weld metal and heat affected zone area were also investigated to achieve more understanding regarding the effect of multiple repairs to the properties of Duplex weldment. Bearing in mind that at the moment, carrying out just one repair per welded joint especially for Duplex Stainless Steel is advised as the limiting condition.